INTERCULTURAL COMMUNICATION PATTERNS OF SANTRI IN BUILDING UKHUWAH - Tamam, M. Badrut; Maskur, Maskur (International Conference on Humanity Education and Society (ICHES), 2025)
The background of this research is the cultural diversity of santri from various regions in Indonesia which poses its own challenges in the communication process and the formation of ukhuwah. This research uses a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The results showed that the intercultural communication patterns of students in boarding schools were dominated by linear and circular communication. The main supporting factors for the establishment of ukhuwah are openness, tolerance, the active role of administrators in guiding students, and the existence of joint activities that are inclusive. However, obstacles that often arise include regional language differences, cultural stereotypes, and ethnocentrism. To overcome these obstacles, the boarding school applies strategies such as using Indonesian as a unifying language, strengthening the values of Islamic brotherhood, and habituation of intercultural interaction through activities at the boarding school. The conclusion of this study is that effective intercultural communication patterns play a significant role in building ukhuwah in a multicultural boarding school environment. With open communication and mutual respect, cultural differences can be managed into strengths to strengthen brotherhood between students. This research is expected to be a reference in developing intercultural communication strategies in the Islamic education environment.